Presenting a model of managerial practical wisdom in hospitals - Mahdavi, Akramsadat; Ardabili, Farzad Sattari; Kheirandish, Mohammad; Ebrahimpour, Habib; Daryani, Shahram Mirzaei (Zielona Góra: Faculty of Economics and Management Press)
References this qualitative study was conducted to provide a model of managerial practical wisdom in public hospitals in order to define the components affecting managerial practical wisdom, development strategies and its results in hospitals based on interpretive paradigm using Grounded strategy and content analysis technique and based on paradigm model of Corbin and Strauss (2008).
Keywords: public hospital; health care management; practical wisdom; development strategies of hospitals; szpital publiczny; zarządzanie służbą zdrowia; strategie rozwoju szpitali